Some notes on the meaning of min 民 (and zhong 眾) in the Tsinghua manuscript *Yin gao 尹誥 (The Announcement of Yin) - Crone, Thomas (Asiatische Studien - Études Asiatiques, 2022)
This article addresses the phenomenon that in the *Yin gao尹誥 (The Announcement of Yin), a pre-imperial Chu manuscript of the 4th century BCE published by Tsinghua University, the words min 民 and zhong 眾 appear to refer to two different groups of people. After reviewing the textual evidence and previous hypotheses on this topic, the author draws attention to the fact that while zhong and min are attributed to geographically distinct regions, they nevertheless seem to be related to each other. The author notes that a similar (though not identical) relationship exists between the zhong and min in the “Pan geng” 盤庚 chapter of the Shangshu 尚書 (Book of Documents) and certain passages of the Chunqiu Zuozhuan 春秋左傳 (Zuo commentary of the Spring and Autumn Annals), where the zhong appear to act as delegates of the min, conveying the ruler’s commands to the min and, in turn, communicating the min’s concerns back to the ruler.<br
Keywords: Chunqiu Zuozhuan 春秋左傳 (Zuo commentary of the Spring and Autumn Annals); min 民; “Pan Geng” 盤庚; *Yin gao 尹誥 (The Announcement of Yin); zhong 眾